Investigation on the risk factor of soccer-related injury from physical maturation aspects - Norikazu, H. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The increasing of mechanical stress which forced during the training and the match is thought to be the risk factor of the soccer-related injury during puberty. It has been reported that the increase of mechanical stress depends on the physical maturation and large individual difference in physical and biological maturation exists during puberty. These findings led us to propose two hypothesizes. First, early-matured adolescents, who may be stronger and bigger, are more likely to suffer from acute traumatic injury. Secondly, it is thought that intensive training may be overly stressful for late matured players as compared to early and average matured players because of their physical weakness. Therefore, in this study we examined the relationship between injury rates and biological maturation in adolescent soccer players. In addition we investigated the other risk factor of the over-use injury during puberty. Mothod One hundred and twenty five well-trained adolescent soccer players aged 12.2±1.5 years old (9.5~14.8 years old) were participated in this study. Participants were divided into three age categories (U11, U13 and U15), four maturational difference (MD: skeletal age-chronological age) groups: Early (MD>1.0), Average (MD= ±1.0), Late (MD>1.0), and four height increment phase (HIP; Phase1 to Phase4) according to their annual height increment. Then relation between injury rate and these maturational statuses were examined. Result The rate of injury increases with age (p<0.01). In U15, late maturity players had the highest occurrence of overuse injury, while early-matured players tended to be vulnerable to acute traumatic injury. Moreover, players whose HIP was determined as phase2 (growth spurt) during the pre-season period had significantly higher rates of overuse injury than any other HIP group (p<0.001). In terms of acute injuries, players in Phase3 (after growth spurt) had the highest injury rate of all the HIP groups (p<0.01). During Phase2, players showed a rapid gain in height. Moreover, in Phase2, 56.9% to 91.7% of proximal tibial apophyses were determined as being in the apophyseal or epiphyseal stage of growth. Discussion These result may imply that relative stress forced by training becomes stronger for late matured players in older age group. Moreover, physical growth and apophyseal fragility are thought to be risk factors for soccer-related injuries. A player who`s pre-season HIP is determined as Phase2 might be more vulnerable to overuse injury. Hence, we believe that evaluating individual pre-season HIP and biological maturity would help coaches and athletic trainers to predict and prevent certain kinds of soccer-related injuries.